1999
DOI: 10.1021/ja991032t
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Studies on the Selectivity of GGG Triplets toward One-Electron Oxidation in B-Form DNA

Abstract: The selectivity of 5‘-TGGGT-3‘ and 5‘-CGGGC-3‘ sequences toward photoinduced one-electron oxidation was examined experimentally and by ab initio molecular orbital (MO) calculations. It was confirmed experimentally that G2 of 5‘-TG1G2G3T-3‘ is more reactive than G1, while for 5‘-CG1G2G3C-3‘ the selectivity is reversed, that is, G1 > G2. The ab initio MO analyses were performed to elucidate the difference of the selectivities between 5‘-TGGGT-3‘ and 5‘-CGGGC-3‘ sequences. For the 5‘-TGGG-3‘ sequence, the spin de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

34
208
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(242 citation statements)
references
References 50 publications
34
208
0
Order By: Relevance
“…In early experiments it was shown that photoexcitation of DNA in its normal B-type double helical form by intense nano-or picosecond 266 nm laser pulses induces a greater damage of guanines positioned on the 5′-side of purine bases, especially adjacent to guanine, than on guanines adjacent to pyrimidines. 7 This selectivity of G oxidation in different sequence context has been also observed employing one-electron oxidants generated by photosensitization of metal complexes, 3,8 anthraquinones, 4,9 naphthalimides, 10 riboflavin (RF), 11,12 4′-pivaloyl derivatives, 13,14 cyanobenzoyl and cyanobenzophenone substituted 2′-deoxyuridine 15,16 and other chemical one-electron oxidants. 17, 18 Saito and co-workers have shown that the enhancement of oxidative guanine damage increases with the number of contiguous guanines according to 5′-G < 5′-GG < 5′-GGG and that this phenomenon is correlated with the calculated gas phase ionization potentials (IP) for guanines in different sequence contexts.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…In early experiments it was shown that photoexcitation of DNA in its normal B-type double helical form by intense nano-or picosecond 266 nm laser pulses induces a greater damage of guanines positioned on the 5′-side of purine bases, especially adjacent to guanine, than on guanines adjacent to pyrimidines. 7 This selectivity of G oxidation in different sequence context has been also observed employing one-electron oxidants generated by photosensitization of metal complexes, 3,8 anthraquinones, 4,9 naphthalimides, 10 riboflavin (RF), 11,12 4′-pivaloyl derivatives, 13,14 cyanobenzoyl and cyanobenzophenone substituted 2′-deoxyuridine 15,16 and other chemical one-electron oxidants. 17, 18 Saito and co-workers have shown that the enhancement of oxidative guanine damage increases with the number of contiguous guanines according to 5′-G < 5′-GG < 5′-GGG and that this phenomenon is correlated with the calculated gas phase ionization potentials (IP) for guanines in different sequence contexts.…”
Section: Introductionmentioning
confidence: 71%
“…[41][42][43] The values of ϕ monotonously increase with increasing concentrations of DNA duplexes (see, Figure S2 in Supporting Information); at a duplex concentration ([duplex]) of 100 μM, practically all BPT molecules are bound to DNA and the ϕ values are in the range of 0.8 to 0.9 for a series of six oligonucleotide duplexes (Table S2, Supporting Information). The binding constants, K = (1.4±0.3)× 10 5 M −1 were obtained by fitting the following equation (12) to the experimental data points ( Figure S2). The values of K are not a function of the number of guanines or of their mode of grouping into separated or contiguous guanines.…”
Section: Fractions Of Bpt Molecules Bound To the Dnamentioning
confidence: 99%
“…Thus, the electronic structure of nucleotides and their ionization properties are essential for understanding the mechanism of DNA damage. Extensive experimental and theoretical studies have focused on these topics (11)(12)(13)(14)(15)(16)(17)(18)(19). In particular, LeBreton and coworkers (9,[20][21][22][23][24] have investigated the ionization of nucleic acid bases, sugar residue, and the phosphate in the gas phase by using UV photoelectron spectroscopy (PES) and then combining these studies and molecular orbital calculations to address the electronic structure of the nucleotides.…”
mentioning
confidence: 99%
“…1), but this was only recently shown experimentally (Zeng & Wang, 2007). New findings show that electron capture and migration along BrdU-substituted DNA might be contra-thermodynamically selective and, thus far more complicated (Yoshioka et al, 1999;Aflatooni et al, 1998). In cells, radiosensitization by BrdU (typically at ~20-30% thymine replacement) gives about 2-3 fold radiotoxicity enhancement and in most cell types parallels similar increase in the DSB yield, and/or the decreased rate of their repair (Sawada & Okada, 1972).…”
Section: Introductionmentioning
confidence: 96%